The effectiveness of counseling to realize the benefits of exercise, exercise behavior and factors associated with diabetes patients - กสิวิทย์อำนวย นิคม; สุจริยากุล อนุพงค์; ชำนาญกิจ พรรวินท์ (Disease Control Journal, 2014)
The effectiveness of counseling to realize the benefits of exercise, exercise behavior and factors associated with diabetes patients. This study was prospective cohort study design. The aims to study the effect of counseling to realize the benefits of exercise, comparing the differences and association between the realize the benefits of exercise, exercise behavior and demographic factors, to determine the predictors of to realize the benefits of exercise and exercise behavior of diabetes patients through the process of group counseling in diabetes clinic in a community hospital in Ratchaburi Province. Data were collected by questionnaire from 239 samples. The study period from May 2012 to May 2014. The descriptive statistics to describe the general characteristics of the sample, presented by frequency, percent, mean, standard deviation, minimum, maximum. The inferential statistics used for testing the hypothesis by comparing the difference between demographic factors, including gender, age, education, occupation, and realize the benefits of exercise for diabetics by the t-test and ANOVA, analysis of the association between demographic factors with realize the benefits of exercise and exercise behavior among patients with diabetes who had the process of group counseling to realize the benefits of exercise used the Pearson’s correlation coefficient, to factors predicted use the multiple regression analysis with Enter and Stepwise method, and determine the level of significance at the 0.05. The results were as follows: most of the samples were female (78.2%), 60 years old (43.1%), followed by 51-60, 40-50 years old, 34.3%, 17.6% and less than 40 years old was 5.0% respectively, age mean 58.6 years old, minimum 21 years old maximum 80 years old. Education level were primary school followed by 78.7%, unschooled 9.2%, secondary school 8.3% and diploma 3.8% a chore 45.6%, followed by contract farming and the government/state-owned enterprises by 18.8%, 16.3%, 14.2% and 5.0%, respectively, with an sufficient exercise 49.0%, did not sufficient exercise 51.0% (did not exercise 8.4%) The realize to benefits of exercise was high level at 88.7%, moderate level at 5.4% and low level at 5.9% with an average score of 5.6 points out of 6 points. The exercise behavior was high level at 77.0%, moderate level at 5.9% and 17.2% was low level, average score 3.9 points out of 5 points. The diabetes patient which had exercise habits could control the blood sugar in standard level more than 85.0%. Demographic factors, including gender, age, education, occupation, did not affect to realize the benefits of exercise and exercise behavior (p>0.05). The swing arm exercise was 89.0%, followed by a brisk 63.0%. The group counseling about the realize the benefits of exercise was positive association with exercise behavior of diabetes patients with statistically significant at the 0.05 level. The factor that could predicted to exercise behavior of patients with diabetes was group counseling is to provide awareness about the realized the benefits of exercise with statistically significant level <0.001.